Synthesis of 1,8-Dioxo-Decahydroacridines using Pyridinium Hydrogen Sulfate Ionic Liquid as an Green, Efficient and Reusable Catalyst - Karimian, Somaye; Tajik, Hassan (Letters in Organic Chemistry, 2016)
Background: In this research, pyridinium hydrogen sulfate ionic liquid (PHSIL) was employed as a green, efficient and reusable catalyst for the synthesis of 1,8-dioxo-decahydroacridines. Different primary amines and aromatic aldehydes were subjected to the reaction with 5,5-dimethyl- 1,3-cyclohexanedione (dimedone) in the presence of this catalyst and the corresponding products were achieved in excellent yields and short reaction times. Two important advantages of the study were easily separation of ionic liquid from the reaction mixture by water extraction and a high recycling capability of up to six times. Methods: Different primary amines and aromatic aldehydes were subjected to the reaction with 5,5-dimethyl-1,3- cyclohexanedione (dimedone) in the presence of, pyridinium hydrogen sulfate ionic liquid (PHSIL) catalyst and the corresponding 1,8-dioxo-decahydroacridines derivatives were achieved in excellent yields and short reaction times. Results: Having established optimum conditions as follows: aldehyde (1 mmol), amine (1 mmol), PHSIL (0.65 mmol), CH3CN (3 mL) at 80°C, a series of 1,8-dioxo-decahydroacridines were synthesized via the one-pot three component reaction between various aromatic aldehydes and amines with dimedone. The aromatic aldehydes containing electrondonating and electron-withdrawing groups afforded 1,8-dioxo-9-aryl-10-aryl-decahydroacridines with high yields within short reaction times in comparison with other conventional procedures. The presence of substituent on the amine has the same effect. All compounds were identified by melting point (in some cases), IR spectra, 1H- and 13C-NMR and elemental analysis. Conclusion: In summary, pyridinium hydrogen sulfate ionic liquid was used as a green catalyst for the synthesize of 1,8- dioxo-decahydroacridines. Various derivatives of acridinediones were synthesized in high yield. Short-time reaction, high yield, stability, reusability up to six times, relatively non-toxicity of the catalyst, economically viable and one-pot synthesis of acridinedione derivatives are the important advantages of the reported method.
Keywords: green chemistry